KAPASITAS GESER BALOK BETON BERTULANG DENGAN OLYPROPYLENE FIBER SEBESAR 4% DARI VOLUME BETON - Apriyatno, Henry (Jurnal Teknik Sipil dan Perencanaan, 2010)
Abstract:ÃÂ  PolypropyleneÃÂ  fiberÃÂ  isÃÂ  oneÃÂ  ofÃÂ  theÃÂ  plasticÃÂ  fiberÃÂ  thatÃÂ  hasÃÂ  highÃÂ  tensileÃÂ  strength,ÃÂ  easily available, relatively cheap, resistant to chemical attack, and has a dry surface so that no clumping of fiber in the concrete mixing process.The study aims to determine the effect of polypropylene fiber by 4% ofÃÂ  the volume of concreteÃÂ  to shear strength ofÃÂ  reinforced concrete beams. The addition of polypropyleneÃÂ  fiberÃÂ  inÃÂ  theÃÂ  levelsÃÂ  ofÃÂ  0%ÃÂ  toÃÂ  4%ÃÂ  ofÃÂ  theÃÂ  volumeÃÂ  ofÃÂ  concreteÃÂ  causesÃÂ  aÃÂ  decreaseÃÂ  in modulus of elasticity of 13966.33 MPa to 11,709 MPa. Shear test results reinforced concrete beam fiberÃÂ  contentÃÂ  increaseÃÂ  fromÃÂ  0%ÃÂ  to 4%ÃÂ  increaseÃÂ  inÃÂ  capacityÃÂ  obtainedÃÂ  byÃÂ  theÃÂ  nominalÃÂ  shearÃÂ  beam from 4.08 tons to 4.56 tons. Fiber concrete beams will increase the shear capacity of 11.76% of the normal beam shear capacity. Keywords: polypropylene fiber, modulus elasticity, shear capacity ÃÂ  Abstrak:ÃÂ ÃÂ  PolypropyleneÃÂ  fiber merupakan salah satu serat plastik yang memiliki kuatÃÂ  tarikÃÂ  tinggi, mudahÃÂ  didapat,ÃÂ  harganyaÃÂ ÃÂ ÃÂ  relatifÃÂ  murah,ÃÂ  tahanÃÂ  terhadapÃÂ  seranganÃÂ  bahanÃÂ  kimia,ÃÂ  danÃÂ  memiliki permukaanÃÂ  yangÃÂ  keringÃÂ  sehinggaÃÂ  tidakÃÂ  terjadiÃÂ  penggumpalanÃÂ  seratÃÂ  dalamÃÂ  prosesÃÂ  pengadukan beton. PenelitianÃÂ  bertujuan untuk mengetahui pengaruh penambahan polypropylene fiber sebesar 4% dari volum beton terhadap kuat geser balok beton bertulang. Penambahan polypropylene fiber dari kadar 0% sampai 4% dari volume beton menyebabkan penurunan nilai modulus elastisitas dari 13.966,33 MPa menjadiÃÂ  11.709 MPa. HasilÃÂ  pengujianÃÂ  geserÃÂ  balokÃÂ  betonÃÂ  bertulangÃÂ  penambahan kadar serat dari 0%ÃÂ  sampai 4% diperolehÃÂ  kenaikanÃÂ  kapasitas geser nominal balok dari 4,08ÃÂ  ton menjadi 4,56ÃÂ  ton.ÃÂ ÃÂ  Balok betonÃÂ  fiber akan mengalami kenaikan kapasitas gesernya sebesar 11,76 % dari kapasitas geser balok normal. ÃÂ  Kata kunci: polypropylene fiber, modulus elastis, kapasitas geser